Studies on Germination, Early Seedling Growth and Development of Castanea sativa - Mohd Rafiee, M T A; Hashimah, Elias; Mohd Effendi, Wasli; Mogeret, Sidi; Meekiong, Kalu; Hafsah, Nahrawi (2021)
Castanea sativa Mill. (sweet chestnut) is a medium large deciduous plant, primarily found distributed from Southern Europe and North Africa, to North-Western Europe and eastward to Western Asia. The species is not only known for its edible seed, but also notable for its lumber (hardwood), which significant as natural resources for food and timber industry. Considering the remarkable uses, this study was conducted since no research was done yet on germination, early growth and development of chestnut in Malaysia. Thus, this preliminary study attempted to investigate at the germination, early seedling growth and development of PA 50 Castanea sativa as well as the occurrence of pest and disease in the nursery. Different sizes of seeds were grown on planting substrates which eventually kept under different growing condition. Results were obtained through examination on shoot and root development while observing any incidence of pest and disease. Data were analysed on seed germination rate (%), seedling growth and development including growth rate (%), seedling emergence (%), root length (cm), shoot length (cm), root collar diameter (cm), pest and disease infestation (%). The findings are feasible for agroforestry especially in the establishment of chestnut in equatorial climate.